CFC Legislation, Passive Assets and the Impact of the ECJ's Cadbury-Schweppes Decision - Martin Ruf; Alfons Weichenrieder (Center for Economic Studies and ifo Institute (CESifo), 2013)
In its Cadbury-Schweppes decision of 12 September 2006 (C-196/04), the Court of Justice of the European Union decided that the UK controlled foreign corporation rules, which were implemented to subject low taxed passive income of foreign affiliates to UK corporate tax, implied an infringement of the freedom of establishment. Consequently, many EU countries including Germany changed their legislation. The paper discusses to which extent the ECJ ruling has impacted on the allocation of passive assets in German multinationals. Using firm level data we find evidence for an increased preference for low-tax European countries compared to non-European countries.
Keywords: H25; H73; 330; Court of Justice of the European Union; corporation tax; foreign direct investment; CFC regulation; passive investment